The Influence of Emotional Regulation on Internet Addiction towards Students Who Use Online Gambling Sites and Applications - Diana Dwi Fortuna; Nurmina (Causalita, 2024)
This study aims to examine the influence of emotion regulation on internet addiction in online gambling site and application users. This study uses a quantitative method with a correlational quantitative design. The population in this study are university students who use online gambling in Indonesia. The sampling technique in this study uses purposive sampling technique with 105 respondents. The instruments in this study use the Internet Addiction Test (IAT) scale (Young, 2017) which has been modified by the researcher to suit online gambling use. Participants' emotional regulation skills were measured using the Difficulties Emotion Regulation (DERS) measurement tool first developed by Gratz and Roemer (2004) which has been adapted into Indonesian by Nina (2014). Data was collected by distributing online and offline surveys using Google Forms and processed using Spearman correlation with the help of spss 25 for windows. The results of the data analysis show a significance of 0.000 <0.05. Emotion regulation has a significant negative relationship with internet addiction so that the higher the emotional regulation score obtained by the subject, the higher the possibility of experiencing internet addiction. This shows that Ha is accepted and Ho is rejected or can also be interpreted that there is an influence of emotion regulation on internet addiction.